Visualising and Valuing Urban Agriculture for Land Use Planning: A Critical GIS Analysis of Sydney and Neighbouring Regions - Joshua Zeunert; Scott Hawken; Josh Gowers (Land)
The loss of a city’s agricultural lands due to land use change through urban development is a global problem, as local food production is an essential green infrastructure for intergenerational sustainability. Like many cities, much of Sydney’s rapid urban development occurs on land previously used for food production. Sydney has one of the highest rates of urban growth among Western cities and a planning strategy that marginalises its agricultural productivity. To better understand and advocate for Sydney’s capacity for food production we explore all available government datasets containing agricultural biophysical capacity using a critical GIS approach. Employing various spatial-data visualisations to contextualise agricultural production, we examine inherent biophysical agricultural capacity in Sydney and comparable regions along the eastern coast of NSW. Our approach interrogates the notion that Sydney’s metropolitan landscape is of low inherent biophysical quality for agriculture, thereby challenging current development and planning orthodoxy and policy. In ascertaining Sydney’s comparative capacity for agriculture we find that, despite current metropolitan planning policy, datasets reveal western Sydney is biophysically well suited for agriculture. Sydney overall is comparable to five of six other coastal regions of NSW and superior to at least two. While acknowledging metropolitan land use complexities that shape agricultural production in practice, we argue for improved critical application and contextual understanding of existing agricultural datasets to better inform future planning policy to advance regional food security and aid long-term sustainability.